PRELIMINARY IDENTIFICATION OF ORGANIZATIONAL CULTURE STYLES IN THE PROCESS OF STRATEGIC PLANNING: EMPLOYEE PERCEPTION IN THE TURKISH PUBLIC HIGHER EDUCATION - Ali Osman Öztürk; Elif Genç Tetik (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
It is widely accepted that culture is an essential element to understand how any organization functions and public sector organizations are certainly not out of this. Comprehending organizational culture is a prerequisite to examine the public sector thoroughly because it forms the essence of all the actions, processes and outcomes in the organizations. Indeed, the vast majority of the previous studies emphasise that the concept has become much relevant with the strategy-making process in the public organizations, which mainly needs to be consistent with the culture types of organization. In times of change, the consistency between culture and strategy is key to create a sustainable organizational structure. The paper primarily intends to explore the culture of a higher education institution in Turkey and investigates to what extent the culture of the institution is ready for an organizational change, which is aimed to be generated through the strategic planning process. The empirical results show that hierarchical culture is seen as the most dominant existing culture among other types, while the desired culture, which the members of the institution would like to embrace, appears to be adhocracy culture. Theoretical, and empirical implications, are investigated throughout the paper.